Two new species of Ulmeritoides Traver (Ephemeroptera: Leptophlebiidae) from Southeastern Brazil - Souto, Paula Malaquias; Da-Sil, Elidiomar Ribeirova; Nessimian, Jorge Luiz; Gonçalves, Inês Corrêa (Zootaxa, 2016)
Two new species of Ulmeritoides Traver, 1959 are described from Southeastern Brazil based on male and female imagos. Ulmeritoides angelus sp. nov. (Holotype male deposited in DZRJ: Minas Gerais State) differs from all other species of the genus by the following combination of characters: forewings hyaline, base dark brown and purplish; veins R1 light brown; dark brown spots on bullae of veins Sc and R2; apex of penis lobes somewhat rounded, each with one central spine. Ulmeritoides tamoio sp. nov. (Holotype male deposited in DZRJ: São Paulo State) differs from all other species of the genus by the following combination of characters: wings hyaline; veins C, Sc and R1 brownish; brownish spots on bullae of veins Sc and R2; apex of penis lobes straight, ending in rather acute apical and mesal projections. An updated key to the genera Ulmeritoides Traver, 1956 and Ulmeritus Traver, 1956 is also given.